As cores e sua influência no processo projetual - Friso, Valéria Ramos; Landim, Paula da Cruz; Silva, João Carlos Riccó Plácido da; Silva, José Carlos Plácido da; Paschoarelli, Luis Carlos [UNESP] (My University, 2013)
In current days, the technology in materials and compounds makes it possible to implement a wide range of colors in any production process is this graphic or product. Formerly the limitations of series production allowed a small variety of colors and reasons, and the consumer had access to few options at the time of purchase. Today the companies make use of color in ceaseless products in order to differentiate them from competitors, which awakens an alert during the creative process of designer: How To properly apply the colors to the products? This Article aims at helping these professionals to understand how it works the Chroma spectrum in their physiology and psychology in such a way as to demonstrate a method to create a palette of colors directed to the user to whom you want to reach. This methodological suggestion, among other possible, should facilitate the process of choice of colors by professional during the creative process and projectual.

Nos dias atuais, a tecnologia em materiais e compostos viabiliza a aplicação de uma grande gama de cores em qualquer processo de produção seja este gráfico ou produto. Antigamente, as limitações da produção em série permitiam uma pequena variedade de cores e motivos, e o consumidor tinha acesso a poucas opções na hora da compra. Hoje, as empresas fazem uso incessante das cores em produtos, a fim de os diferenciar dos concorrentes, o que desperta um alerta durante o processo criativo dos designer: Como aplicar adequadamente as cores aos produtos? Este artigo objetiva auxiliar estes profissionais a entenderem como funciona o espectro cromático na sua fisiologia e psicologia, de maneira a demonstrar um método de criar uma paleta de cores direcionada para o usuário que se pretende atingir. Essa sugestão métodologica, entre outras possíveis, deve facilitar o processo de escolha das cores pelo profissional durante o processo criativo e projetual.
Keywords: Colors; Design; Methodology projetual; Cores; Design; Metodologia projetual